(untitled) (Journal of Health, Population and Nutrition, 2009)
Despite gains in controlling mortality relating to diarrhoeal disease, the burden of disease remains unacceptably high. To refocus health research to target disease-burden reduction as the goal of research in child health, the Child Health and Nutrition Research Initiative developed a systematic strategy to rank health research options. This priority-setting exercise included listing of 46 competitive research options in diarrhoeal disease and their critical and quantitative appraisal by 10 experts based on five criteria for research that reflect the ability of the research to be translated into interventions and achieved disease-burden reduction. These criteria included the answerability of the research questions; the efficacy and effectiveness of the intervention resulting from the research; the maximal potential for disease-burden reduction of the interventions derived from the research; the affordability, deliverability, and sustainability of the intervention supported by the research; and the overall effect of the research-derived intervention on equity. Experts scored each research option independently to delineate the best investments for diarrhoeal disease control in the developing world to reduce the burden of disease by 2015. Priority scores obtained for health policy and systems research obtained eight of the top 10 rankings in overall scores, indicating that current investments in health research are significantly different from those estimated to be the most effective in reducing the global burden of diarrhoeal disease by 2015. Key words: Child heath; Diarrhoeal diseases; Mortality; Priority setting; Medical research To download the table in Excel format, please go to the Side Bar on the right and click on Supplementary Files. doi: 10.3329/jhpn.v27i3.3374 J Health Popul Nutr 2009 Jun;27(3):319-331